(untitled) (Historia, 2021)
In December 1982, four explosions occurred at Africa’s only nuclear power plant, Koeberg. Situated north of Cape Town, a fully on-steam Koeberg could have spread radioactive material over a very large populated area. The banned, and apartheid-designated terrorist organisation, the African National Congress (ANC), regarded by the South African government as a Muscovite client, accepted responsibility for the attack which was designed to hit at the heart of white South Africa and its security apparatus. While the ANC won the propaganda war in this instance, the South African government suffered a humiliating political and economic blow. This article shows that the Koeberg attack took place during a new phase in the ANC’s liberation struggle, a phase which used small operational units to, inter alia, target state-owned energy facilities. The attack on Koeberg is also indicative of the ANC’s opposition to the development and maintenance of a nuclear weapons programme and nuclear weapons in South Africa at a time when the country was being increasingly isolated on account of its suspected nuclear weapons programme. Vier ontploffings het in Desember 1982 by die enigste kernkragstasie in Afrika, die Koebergkernkragstasie, plaasgevind. Indien die kernkragstasie operasioneel was, sou die radioaktiewe materiaal daarvan ’n groot bevolkte gebied rondom Kaapstad affekteer. The verbanne en verklaarde terroriste organisasie, die African National Congress (ANC), ’n Moskou-klient, het verantwoordelikheid aanvaar vir die aanval, wat ten doel was om die veiligheid van blanke Suid-Afrika te bedreig. Die ANC het die propagandastryd in hierdie geval gewen en het die Suid-Afrikaanse regering ’n vernederende politieke en ekonomiese nekslag toegedien. Die artikel dui aan dat die aanval op Koeberg deel was van ’n nuwe fase in die ANC se bevrydingstryd teen apartheid - ’n fase waarin die organisasie met behulp van kleiner operasionele eenhede hoofsaaklik staatsbeheerde energie-installasies aangeval het. Die aanval op Koeberg dien as ’n voorbeeld van die ANC se opposie teen die land se ontwikkeling en instandhouding van ’n kernwapenprogram en kernwapens tydens Suid-Afrika se internasionale afsondering en vermoede van die kernwapenprogram.